PROBLEMATIKA DAN TINDAKAN GURU DALAM MENGHADAPI ANAK BERKEBUTUHAN KHUSUS DI MI NW TANAK BEAK - Iva Nurmawanti; Linda Feni Haryati; Radiusman Radiusman; Ashar Pajarungi Anar; Setiani Novitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
Children with Special Needs (ABK) have the same rights to obtain an education as a normal child. Based on this, MI NW Tanak Beak received the mandate to organize inclusive education in West Lombok Regency. There are 47 children with special needs in the school who are spread in each class. Each crew is unique and requires different treatments. The teacher plays a major role in this matter. Therefore this study will describe the problems that arise from a teacher of the inclusive class and the actions of teachers in solving these problems. This research is qualitative. Data collection was carried out by interviewing a teacher who had not received training on inclusive education and taught in classes with special needs. The results of the study showed that teachers have difficulty in planning activities, implementing learning in the classroom, and interacting with ABK to fulfill their rights. To solve these difficulties the teacher believes that an effective way is to continue to learn about inclusion education, giving affection, attention, assertiveness, discipline, and inculcation of religious values.